2001
DOI: 10.1007/pl00000241
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of acute flurbiprofen and ketoprofen toxicity in rat gastric mucosa at therapy-relevant doses

Abstract: These data show that FBP- and KP-induced amplification of acid injury in the rat gastric mucosa is a sensitive assay whereby, with single drug dosing, the gastrotoxic potential of these and other NSAIDs may be estimated at therapy-relevant doses that in humans threaten mucosal integrity only following chronic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Indeed, a recent study by our group showed that another CINOD, the NO-donating flurbiprofen HCT 1026, was effective in slowing muscle dystrophy and that, at least in animal models, it was superior to the glucocorticoid prednisolone [18]. However, flurbiprofen produces severe gastrointestinal damage which makes it unsuitable for long-term treatment, especially in paediatric patients [46]. Therefore, we have focused on NCX 320 because it is based on ibuprofen, whose profile of safety and tolerability is well established and consequently is accepted for paediatric use [47].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study by our group showed that another CINOD, the NO-donating flurbiprofen HCT 1026, was effective in slowing muscle dystrophy and that, at least in animal models, it was superior to the glucocorticoid prednisolone [18]. However, flurbiprofen produces severe gastrointestinal damage which makes it unsuitable for long-term treatment, especially in paediatric patients [46]. Therefore, we have focused on NCX 320 because it is based on ibuprofen, whose profile of safety and tolerability is well established and consequently is accepted for paediatric use [47].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, R-flurbiprofen does not inhibit cyclooxygenase activity [4] and has been considered as the non-functional constituent of marketed flurbiprofen-racemate. However, R-flurbiprofen reduces inflammation [5] via inhibition of the transcription factor NF-κB [5] and is essentially free of the side effects typical to classical NSAIDs, such as gastrointestinal or renal toxicity [6]. Because of the anti-inflammatory efficacy and essential lack of toxicity R-flurbiprofen has been evaluated as a potential remedy in Alzheimer's disease with some success in clinical trials [7].…”
Section: Introductionmentioning
confidence: 99%
“…The profens are racemates, and their ability to block arachidonic acid oxygenation is associated with the (S)-enantiomers. However, (R)-flurbiprofen is analgesic in humans with modest enantioconversion in vivo and has a better gastrointestinal safety profile than the (S)-enantiomer (L€ otsch et al 1995;Holzer et al 2001). Bishay et al (2010) found that systemically administered (R)-flurbiprofen alleviated mechanical hyperalgesia, cold allodynia and cold hyperalgesia in the spared nerve injury model of neuropathic pain accompanied by a normalisation of AEA levels in the dorsal root ganglia, dorsal horn and forebrain.…”
Section: Oxygenating Enzymes (Cox-2)mentioning
confidence: 97%